PERTANGGUNGJAWABAN HUKUM PENJUAL TERHADAP BARANG CACAT DALAM TRANSAKSI E-COMMERCE BERDASARKAN PERJANJIAN ELEKTRONIK - Diani Zahra Hapsari; Lucky Dafira Nugroho (Yurisprudentia: Jurnal Hukum Ekonomi, 2025)
The advancement of information technology has significantly increased electronic commerce (e-commerce) transactions. While offering convenience and efficiency, this shift in consumer behavior has also raised legal concerns, particularly when consumers receive defective or non-conforming goods. This study examines the legal responsibility of business actors in e-commerce transactions involving defective products, using a normative juridical approach that refers to existing laws and legal literature in Indonesia. Based on Article 19 of Law Number 8 of 1999 on Consumer Protection, business actors are subject to strict liability for any losses incurred due to defective or inappropriate goods. This responsibility applies without the need for the consumer to prove any fault or negligence. The findings indicate that the strict liability principle provides a solid legal foundation for consumer protection. The legal framework ensures that businesses are accountable for the quality of products offered through digital platforms. Consistent law enforcement and greater awareness among business actors regarding consumer rights serve as essential efforts to build a fair and trustworthy digital trade environment. With the rapid transformation of the economic landscape through digitalization, safeguarding consumer interests and maintaining balance between the parties involved in e-commerce become critical components of a stable and credible marketplace.